A-34 An Investigation of Sports Concussion Reporting in Collegiate Club Rugby Players. (13th July 2022) - Patoilo, M; Porter, B; Hanayik, T; Rorden, C; McCall, M
Abstract: Purpose: The current study investigates concussion-reporting among U.S. collegiate club rugby players. There is robust evidence that a large proportion of college-aged athletes have sustained unreported concussions and non-disclosure is partially influenced by sport. Despite college rugby being the fastest growing collegiate sport in America, there is no research on concussion-reporting in U.S. college-aged club rugby players. It is predicted that these players self-report significantly fewer professionally diagnosed concussions than total concussions sustained. Methods: Participants completed a survey about health, sports, and concussion history as part of a larger study on cognitive performance following concussion. Participants included 14 male, club rugby athletes (M = 19.62 years old, SD = 0.96, range = 18–21) recruited from a university in the southeast United States. Exclusion criteria included an existing or prior learning disability diagnosis, ADHD, or other serious neurological issues. Results: Participants self-reported experiencing a significantly higher number of concussions (M = 2.29, SD = 1.44) than were documented by a professional (M = 0.93, SD = 0.73); t(13) = 2.85, p = 0.01). Details were provided for 32 total concussions, and 69% (N = 22) were considered rugby related. Of note, 28.6% of participants (N = 4) reported having none of their concussions diagnosed by a professional, and 35.7% of participants (N = 5) indicated their first concussion was never diagnosed. Conclusions: Concussion non-disclosure is a significant issue among college-aged U.S. club rugby athletes. As rugby continues to be a high-contact and internationally popular sport, additional research is needed to understand these reporting behaviors. Current findings highlight the need for efforts to better understand how coaches and those who work with these athletes can promote and increase accurate concussion-reporting.